THE ROLE OF POLITICAL ADVERTISING IN COMMUNICATIVE ACTIVITIES AS A FACTOR IN THE FORMATION OF IMAGES OF THE LEADER - Koval , Vitalii (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2021)
The article defines the formation of images of the leader through political advertising, analyzes the concepts of "communication", "leader", "social demand", "political advertising", explores the role of social demand for leaders, information factors in the formation of images of the leader. The peculiarities of the formation of the image of a leader in advertising, in particular political, in the process of communicative activity, the essence of the concept of leadership, and ways of its formation are highlighted. The principle of the emergence of a social demand for leadership, the preconditions and consequences of the actions of political advertising in society are studied. Taking into account the qualitative characteristics of society, the attitude of the public to social change, to the leadership of individuals, ways of interacting with each other is determined.The relevance of the article is determined by modern realities in terms of active informatization, politics, socialization and "digitalization" of society in a democracy. The interdependence of society and government, the principles of public formation of politicians, and the effectiveness of their existence in the communicative space, the role of image strategies, political advertising technologies, tasks, components and features of political advertising, other factors influencing the formation of political leader.Understanding political and social advertising in the context of communicative activities provides an understanding of modern social communication processes. Due to social processes, they become more and more complex every year, as new tools of advertising influence and new barriers to the trust of the target audience appear. In particular, voters have their own habits of determining sympathy for certain parties or political leaders, which are difficult to change. However, the rational formation of images of elites makes it possible to form the right messages for society.The problem is that the effectiveness of methods of forming the image of a leader depends on the chosen strategy and characteristics of certain parts of society. Studies of the peculiarities of society, their characteristics and social demands allow you to effectively manage the process of becoming a leader. Given the changing social dynamics of society, in the article we also showed that some leaders no longer meet modern requirements, and then they are replaced by others. The article analyzes the system of counteractions, as a result of which the social dynamics of change of leaders in society is possible.